2020
DOI: 10.1002/ccd.28931
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Impella‐supported high‐risk nonemergent percutaneous coronary intervention in a large single‐center registry

Abstract: Objectives: We aimed to evaluate the early and one-year outcomes of Impellasupported high-risk nonemergent percutaneous coronary intervention (PCI). Background: The evidence for the use of mechanical circulatory support (MCS) devices in high-risk nonemergent PCI is limited and nonconclusive. Methods: We performed a single-center retrospective study including all patients who underwent high-risk nonemergent PCI supported by Impella 2.5/CP at our institution between January 2009 and June 2018. This patient popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…More extensive revascularization was associated with improved 90-day MAE compared Also, the comparison of mortality and adverse event rates across these studies is challenging given the variable baseline patient characteristics and the threshold for device usage. Nonetheless, the allcause mortality at 1-year among patients supported with Impella during HR-PCI were similar at 15.6% in the IMP-IT registry58 and 15.3% in the analysis by Azzalini et al21 Burzotta et al investigated the effect of extent of revascularization on LVEF and survival in 86 patients undergoing Impella-supported PCI in the Roma-Verona registry 59. At a mean follow-up of 14 months, the all-cause mortality rate was 10%.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…More extensive revascularization was associated with improved 90-day MAE compared Also, the comparison of mortality and adverse event rates across these studies is challenging given the variable baseline patient characteristics and the threshold for device usage. Nonetheless, the allcause mortality at 1-year among patients supported with Impella during HR-PCI were similar at 15.6% in the IMP-IT registry58 and 15.3% in the analysis by Azzalini et al21 Burzotta et al investigated the effect of extent of revascularization on LVEF and survival in 86 patients undergoing Impella-supported PCI in the Roma-Verona registry 59. At a mean follow-up of 14 months, the all-cause mortality rate was 10%.…”
mentioning
confidence: 68%
“…Despite the ability for optimization of hemodynamics, the risks associated with the large-bore access for all these mechanical support devices include bleeding and vascular complications. [18][19][20][21][22]…”
Section: Percutaneous Hemodynamic Support Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bleeding complications over time demonstrated that the variability in bleeding risk seen across centres has not changed meaningfully over the last 15 years (Figure 1). 7,[11][12][13][14][15][16][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Given the broad scope of bleeding complications (comprising both access and non-access-related bleeding during PCI), often complicated by pre-existing anaemia and the inclusion of some urgent HR-PCI patient populations, this variability is not surprising. Likewise, many series reported relatively low numbers of cases over extended time periods, suggesting that any advantages of increased operator skill, using best practices accrued through increasing experience, could not be ascertained.…”
Section: Trends In Bleeding and Vascular Complications Over Timementioning
confidence: 99%
“…33,34 The rate of vascular complications remained consistently low over time ( Figure 2). 7,[11][12][13][14][15][16][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Transfusion rates suggest a downward trend over time (Figure 3). Thus, in the absence of Level 1 evidence and specific guidelines for pVAD support during HR-PCI, variation in approaches further add to the difficulty in analysing overall procedural risk as well as bleeding risk.…”
Section: Trends In Bleeding and Vascular Complications Over Timementioning
confidence: 99%